A Correlational Study of Spiritual Well-being and Depression in the Adult Cancer Patient. Issue 2 (April 2017) - Stutzman, Hannah; Abraham, Sam
Abstract : Depression in adult cancer patients has been widely studied, along with spiritual effects of traumatic events and even spiritual growth after a diagnosis of cancer. There has been limited research determining a direct correlation between spiritual well-being and depression in adult cancer patients. The purpose of this research study was to examine the relationship between spiritual well-being and depression in adult cancer patients. This was a descriptive correlational study using 59 patients older than 18 years from an outpatient cancer center. The researchers hypothesized that patients with a low spiritual well-being score would be more likely to have a high depressive symptom score, thus providing support for a correlation between cancer patient's spiritual well-being and risk of depression. Implications of this study lead to evidence for better screening processes for cancer patients regarding spiritual well-being.